2016
DOI: 10.1017/s0954422416000226
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms responsible for the hypocholesterolaemic effect of regular consumption of probiotics

Abstract: CVD affect a large proportion of the world's population, with dyslipidaemia as the major risk factor. The regular consumption of both probiotic bacteria and yeast has been associated with improvement in the serum lipid profile. Thus, the present review aims to describe and discuss the potential mechanisms responsible for the hypocholesterolaemic effect of regular consumption of probiotic bacteria and yeast. Regarding the hypocholesterolaemic effect of probiotic bacteria, the potential mechanisms responsible in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 84 publications
(124 reference statements)
2
54
0
4
Order By: Relevance
“…The potential probiotic mechanisms related to the hypocholesterolemic effect could involve active bile salt hydrolase (BSH), cholesterol co-precipitation with deconjugated bile salts, bacterial cell membrane assimilation and incorporation of cholesterol, conversion of cholesterol to coprostanol through the cholesterol reductase enzyme and SCFA production [207]. The BSH increased fecal excretion of free bile acids, preventing their reabsorption and compensatory increased use of cholesterol to produce bile acids, which could lead to a reduction in the cholesterol present in serum.…”
Section: Probiotic Administration Microbiota Bile Acids and Cardiovmentioning
confidence: 99%
“…The potential probiotic mechanisms related to the hypocholesterolemic effect could involve active bile salt hydrolase (BSH), cholesterol co-precipitation with deconjugated bile salts, bacterial cell membrane assimilation and incorporation of cholesterol, conversion of cholesterol to coprostanol through the cholesterol reductase enzyme and SCFA production [207]. The BSH increased fecal excretion of free bile acids, preventing their reabsorption and compensatory increased use of cholesterol to produce bile acids, which could lead to a reduction in the cholesterol present in serum.…”
Section: Probiotic Administration Microbiota Bile Acids and Cardiovmentioning
confidence: 99%
“…A prebiotic effect cannot on the other hand be ruled out, leading to an increased synthesis of SCFA (especially propionate), which, after absorption, may act as an inhibitor of cholesterol synthesis in the liver (Reis et al 2017). At high dosage, betaglucan also improves postprandial glycemic response (Ho et al 2016).…”
Section: Fibermentioning
confidence: 99%
“…Several possible mechanisms for cholesterol's intestinal removal by probiotics have been proposed (Shimizu et al 2015). Examples include binding of cholesterol to cell surface (in a fashion similar to that of PS of fiber), uptake of cholesterol by growing cells, deconjugation of bile via bile salt hydrolase and subsequent coprecipitation of cholesterol, and some unclear physiological actions of shortchain fatty acid fermentation (Reis et al 2017).…”
Section: Probioticsmentioning
confidence: 99%
“…One interesting example is an application of these microorganisms as a non-pharmaceutical approach to help manage human metabolic disorders [1]. In this regard, research from several laboratories around the word has demonstrated that the regular consumption of probiotics is able to improve the serum lipid profile, in particular by reducing serum cholesterol levels.…”
mentioning
confidence: 99%
“…In this regard, research from several laboratories around the word has demonstrated that the regular consumption of probiotics is able to improve the serum lipid profile, in particular by reducing serum cholesterol levels. Moreover, scientists have shown that the hypocholesterolaemic effect of probiotics could be explained by different mechanisms that include: decreased absorption of intestinal cholesterol, deconjugation of bile salts; modulation of lipid metabolism through changes in cytokine and adipokine profiles, incorporation or assimilation of cholesterol in the bacterial membrane, and inhibition of the expression of the intestinal cholesterol transporters [1]. More recently, the search for beneficial effects of probiotics on metabolism has moved to the modulation of serum uric acid levels.…”
mentioning
confidence: 99%